Selection of LTE's Duplex Mode for CDMA Operator - Leming Hu (Dianxin kexue)
The issue of selection of LTE's duplex mode for CDMA operator was discussed. Based on detail analysis on involved factors, it was pointed out that CDMA operator might suffer some serious problems if TDD mode was selected.